Prevalence and epidemiological characteristics of inmates diagnosed with infectious diseases living in a region with a high number of prisons in Sao Paulo state, Brazil - Nascimento, Charlene Troiani do; Pena, Danilo Zangirolami; Giuffrida, Rogerio; Bandeira Monteiro, Fernanda Nobre; Silva, Francisco Assis da; Flores, Edilson Ferreira [UNESP]; Prestes-Carneiro, Luiz Euribel (Bmj Publishing Group, 2020)
Objective To determine the prevalence and epidemiological characteristics of inmates diagnosed with infectious diseases living in a region with a high number of prisons, Sao Paulo, Brazil. Design This is a retrospective and descriptive study conducted from November 2017 to October 2018. Setting Prisons located in the western and northwestern regions of Sao Paulo, Brazil. Methods We conducted a retrospective analysis on infectious diseases and coinfections (HIV, hepatitis B virus (HBV), hepatitis C virus (HCV), syphilis and tuberculosis (TB)) of inmates from 28 prisons. Inmates were previously diagnosed following the protocol for control and surveillance of infectious diseases, through laboratory or imaging methods. A questionnaire was completed by the healthcare staff. Prevalence was obtained by dividing the number of individuals with positive results by the number of inmates in each prison. Locations of prisons were obtained and maps were constructed using geographic information systems. Results A total of 741 of 37 497 inmates (1.97%) were diagnosed with HIV, HBV, HCV, syphilis or TB. HIV was the most prevalent infectious disease (0.68%), followed by TB (0.66%), syphilis (0.2%), HCV (0.2%) and HBV (0.04%). For all of these diseases, prevalence rates varied from very low to high (3.11% and 2.45%) for TB and HIV, respectively, in the five prisons where they were most prevalent. HIV-syphilis was the most associated coinfection (OR, 63.7; 95% CI 41.4 to 96.7). Three of those diagnosed with the infection were female and the ratio of female to men was 0.004:1. Conclusions Our findings demonstrate that the number of cases of infectious disease among inmates in the northwestern and western region of Sao Paulo is probably underestimated, with lower rates of HCV, HBV and syphilis. This represents a challenge to prisoners' health. Improvements in diagnosis, mainly to reduce viral hepatitis, are crucial with benefits for inmates and the general population.
Keywords: epidemiology; public health; geographical mapping; general medicine (see internal medicine)